Authorisation of Abortion for a "Serious Danger to Mental Health": Would the Practice Stand up to the Judicial Test? - Dixon, Amy (Victoria University of Wellington Law Review, 2012)
In Right to Life New Zealand Inc v The Abortion Supervisory Committee, Miller J observed that, "there is reason to doubt the lawfulness of many abortions authorised by certifying consultants". This article questions this observation through an interpretation of "serious danger … to … mental health", the most commonly cited ground for authorisation of abortion. Is "mental health" limited to "absence of mental illness" or does it also include "mental wellbeing", which might allow for a more liberal practice? The narrow definition would accord with one objective of the abortion scheme to respect the rights of the unborn child. The wider definition would allow certifying consultants to freely exercise their medical judgement, a condition on which the abortion scheme is based. This article argues that the latter argument is potentially stronger, but its success rests on the willingness of the judiciary to engage in ambulatory statutory interpretation in the controversial context of abortion. This article concludes by noting that a finding in favour of the narrow definition of mental health still confers substantial flexibility on consultants in assessing danger of mental illness. Finally, this article recommends that Parliament intervene to make the law certain.